Implementasi Media Pembelajaran pada Mata Pelajaran Instalasi Penerangan Listrik di SMK Negeri 1 Rao Selatan - Mardiana, Mardiana; Sukardi, Sukardi (Lembaga Yasin AlSys, 2024)
The study aims to determine the effectiveness of the application of video learning media on student learning outcomes in the subject of Electrical Lighting Installation class XI Electricity Engineering SMK Negeri 1 Rao Selatan. This research was conducted because the use of learning media that has been used so far has not shown significant changes in student learning outcomes, this can be seen from the low student learning outcomes, the cause is the teaching factor that is still centered on the teacher so that students are not active during classroom learning. Therefore, it is necessary to conduct research by applying the use of video learning media during the learning process to see the effectiveness of student learning outcomes. This research used experimental method. The research subjects were students of class XI TITL 1 and 2 SMK Negeri 1 Rao Selatan who were registered in the 2023/2024 school year, totaling 24 and 23 people in each class. Based on the analysis of student posttest data in the experimental class, as many as 87.5% of students managed to achieve scores above the KKM. The results of the effect size calculation are included in the large category. The t test results showed that there was a significant difference between the experimental and control classes in the posttest test. Thus the implementation of video learning media is declared effective in learning Electrical Lighting Installation.